Molecular mechanisms for magnesium-deficiency-induced leaf vein lignification, enlargement and cracking in Citrus sinensis revealed by RNA-Seq. (26th October 2020) - Ye, Xin; Huang, Hui-Yu; Wu, Feng-Lin; Cai, Li-Ya; Lai, Ning-Wei; Deng, Chong-Ling; Guo, Jiu-Xin; Yang, Lin-Tong; Chen, Li-Song
Abstract: Citrus sinensis (L.) Osbeck seedlings were fertigated with nutrient solution containing 2 [magnesium (Mg)-sufficiency] or 0 mM (Mg-deficiency) Mg(NO3 )2 for 16 weeks. Thereafter, RNA-Seq was used to investigate Mg-deficiency-responsive genes in the veins of upper and lower leaves in order to understand the molecular mechanisms for Mg-deficiency-induced vein lignification, enlargement and cracking, which appeared only in the lower leaves. In this study, 3065 upregulated and 1220 downregulated, and 1390 upregulated and 375 downregulated genes were identified in Mg-deficiency veins of lower leaves (MDVLL) vs Mg-sufficiency veins of lower leaves (MSVLL) and Mg-deficiency veins of upper leaves (MDVUL) vs Mg-sufficiency veins of upper leaves (MSVUL), respectively. There were 1473 common differentially expressed genes (DEGs) between MDVLL vs MSVLL and MDVUL vs MSVUL, 1463 of which displayed the same expression trend. Magnesium-deficiency-induced lignification, enlargement and cracking in veins of lower leaves might be related to the following factors: (i) numerous transciption factors and genes involved in lignin biosynthesis pathways, regulation of cell cycle and cell wall metabolism were upregulated; and (ii) reactive oxygen species, phytohormone and cell wall integrity signalings were activated. Conjoint analysis of proteome and transcriptome indicated that there were 287 and 56 common elements between DEGs and differentially abundant proteins (DAPs) identified in MDVLL vs MSVLL and MDVUL vs MSVUL, respectively, and that among these common elements, the abundances of 198 and 55 DAPs matched well with the transcript levels of the corresponding DEGs in MDVLL vs MSVLL and MDVUL vs MSVUL, respectively, indicating the existence of concordances between protein and transcript levels.